1993
DOI: 10.1177/101269029302800104
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Policy and the Welfare State: A Framework for Comparative Analysis

Abstract: This paper sketches out a framework for the comparative analysis of physical exercise policy within the context of the development of the welfare state. The term "physical exercise policy" is used here to refer to specific policies pertaining to the body which were geared towards the fostering of "physical fitness" and specific sport practices. The first section presents general considerations for comparative analysis. Section two discusses a "Society-State" framework. The concluding section presents direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…(Burriel and Puig, 1999). This relates to a general perception of the need for public authorities to adopt a hegemonic position at a particular point in time (Harvey;Beamish&Defrance, 1993:58).…”
Section: The Clubs In the Sports Systemmentioning
confidence: 99%
“…(Burriel and Puig, 1999). This relates to a general perception of the need for public authorities to adopt a hegemonic position at a particular point in time (Harvey;Beamish&Defrance, 1993:58).…”
Section: The Clubs In the Sports Systemmentioning
confidence: 99%
“…Research on international sport policy has shown sport participation opportunities are different from one nation to the next (Chalip, Johnson, & Stachure, 1996;Green, 2005;Palm, 1991;Stahl, Rutten, Nutbeam, & Kannas, 2002) and different levels of sporting opportunity are emphasized quite differently depending on the politics, history, and ideology of that nation and its policy makers (Chalip, 1995;Green & Oakley, 2001;Harvey, Beamish, & Defrance, 1993). Also, many international studentathletes develop their athletic abilities in the club system, which is quite different from the school-based system used in the United States (Rubingh & Broeke, 1998).…”
Section: Transition From High School To Collegementioning
confidence: 99%
“…These articles discuss the importance of historical and political context of sport policy development and look at the major building blocks for sport policy development, such as economics, opportunity for all, and elite sport construction. Harvey, Beamish, and Defrance (1993) developed a framework for the comparative analysis of exercise policies in "welfare" states, or countries where the "state accepts responsibility for the provision of comprehensive and universal welfare for its citizens" (Spicker, 2006, Introduction section, para 1), setting up future multi-nation studies. Exercise policies refer to specific national policies pertaining to the body and initiated to develop physical fitness and sport practices among a nation's citizens.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations